Fiscal Federalism and Regional Growth : Evidence from the Russian Federation in the 1990s - Desai, Raj M. (World Bank, Washington, DC, 2014)
Subnational fiscal autonomy-the basis for fiscal federalism in modern federations-is meant to serve two roles. First, local control over revenue collection is meant to provide a check on the capacity of central authorities to tax arbitrarily local capital. Second, retention of taxes raised locally is meant to establish incentives for subnational governmental authorities to foster endemic economic growth as a way of promoting local tax bases. But in the Russian Federation, fiscally autonomous regions have often resisted market-oriented reforms, the enactment of rules protecting private property, and the dismantling of price controls and barriers to trade. The authors find statistical evidence in support of the hypothesis that fiscal incentives of the Russian regions represent an important determinant of regional economic performance. The authors also seek to understand the conditions under which fiscal autonomy prompts regional growth and recovery, and the conditions under which it has adverse economic effects. They argue that the presence of "unearned" income streams-particularly in the form of revenues from natural resource production or from budgetary transfers from the central government-has turned regions dependent on these income sources into "rentier" regions. As such, governments in these regions have used local control over revenues and expenditures to shelter certain firms (natural resource producers or loss-making enterprises) from market forces. Using new fiscal data from 80 Russian regions from 1996-99, the authors test this central hypothesis in both single- and simultaneous-equation specifications. Their results indicate that tax retention (as a proxy for fiscal autonomy) has a positive effect on the cumulative output recovery of regions since the breakup of the Soviet Union. But they also find that this effect decreases as rentable income streams to regions increase.